Electrocoagulation Column for the Removal of Chromium from Tannery Wastewater: Adsorption Kinetics and Sludge Recovery - Nahid M. Genawi; Nafis Mahmud; Elfatih A. Hassan; Muftah H. El‐Naas (ChemistryOpen)
Electrocoagulation is an efficient electrochemical technology used for the treatment of contaminants in wastewater with reportedly high efficiency in treating chromium‐rich wastewater. In this study, the removal of chromium (III) ions from tannery wastewater by electrocoagulation is investigated at different pH, current density, and chromium concentrations. The complete removal of chromium ions is achieved at a pH of 6.5, current density of 10.0 mA cm−2, and chromium concentration of 500 mg L−1 in batch experiments within an hour. The results showed that the formation of coagulant species during the first 30 min facilitated the chromium removal efficiency through both electrocoagulation and adsorption at low pH of 4. When taking into account varying adsorbent mass, the acquired adsorption kinetics data demonstrates an excellent fit to the pseudo‐second‐order model, predicting a chromium absorption of 5000 mg g−1 compared to the experimental uptake of 5108 mg g−1. In contrast, the experimental and calculated uptakes for fixed adsorbent mass were 5108 and 83333 mg g−1, respectively. The observed discrepancy in the uptake when using fixed mass confirms the advantage of considering the variable adsorbent mass for predicting the adsorption during electrocoagulation. Moreover, 97% of chromium was recovered from the generated sludge using 4% H2SO4 which can ensure the minimization of the hazardus sludge disposal.